APPLICATION OF 14C METHOD TO CHRONOLOGY OF THE CROATIAN DINARIC KARST—A CASE OF THE PLITVICE LAKES. Issue 4 (25th August 2022) - Krajcar Bronić, Ines; Barešić, Jadranka; Sironić, Andreja
ABSTRACT: Karst environments preserve some of the best archives of past climate, vegetation, hydrology, anthropogenic impact, and landscape evolution providing that a reliable chronology can be established. Here we present an example of the system of the Plitvice Lakes (Dinaric karst, Croatia), which is characterized by intensive tufa and lake sediment formations. The radiocarbon dating method, combined with some other dating methods and various geochemical and isotope analyses, showed that the Plitvice Lakes system in the present form has existed for about 8000 years. Older tufa deposits were dated to warm interglacial periods. A long-term comprehensive multi-proxy study showed that all environmental compartments (atmosphere, various water bodies, soil, bedrock, DIC, terrestrial and aquatic biota, and of course various secondary carbonates) must be included in order to obtain trustworthy results.